2013
DOI: 10.14419/ijaes.v2i1.1485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Mandatory Adoption of IFRS on Real and Accruals-based Earnings Management: Empirical Evidence From France

Abstract: The main purpose of this study is to examine whether the mandatory IFRS adoption within French listed companies provides higher earnings quality. More precisely, we study the impact of mandatory IFRS adoption on two approaches of earnings management: real and accruals-based earnings management. This study focuses on a sample of 1488 firm-year observations, 124 firms drawn from the 250 French-listed companies during the period from 1999 to 2011. We use the panel data for our analysis. Specifically, the FGLS est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
4
7
0
2
Order By: Relevance
“…= -0.157, Sig = 0.000), suggesting that the mandatory adoption of IFRS by French companies are associated with less real management. This result is consistent with the literature that suggests that the mandatory IFRS adoption improve earnings quality by restraining the manager's opportunism when managing the real business decisions, Sellami and Fakhfakh (2014). Besides, contrary to the assumption of the political costs arising from the positive theory of accounting, the firm size (SIZE) has a positive and significant effect on the level of the REM.…”
Section: Simultaneous Equations Model Resultssupporting
confidence: 91%
“…= -0.157, Sig = 0.000), suggesting that the mandatory adoption of IFRS by French companies are associated with less real management. This result is consistent with the literature that suggests that the mandatory IFRS adoption improve earnings quality by restraining the manager's opportunism when managing the real business decisions, Sellami and Fakhfakh (2014). Besides, contrary to the assumption of the political costs arising from the positive theory of accounting, the firm size (SIZE) has a positive and significant effect on the level of the REM.…”
Section: Simultaneous Equations Model Resultssupporting
confidence: 91%
“…This was represented by a massive increase in the adjusted R 2 figure from 28% before the adoption of IFRS to 79% after the adoption of IFRS. The finding of the study was in agreement with the works of Ismail et al (2013), Sellami and Fakhfakh (2013), Assidi and Omri (2012) and Sun et al (2011). The findings of Ames (2013), Nullah (2013) and Hoque et al (2012) however stipulated that IFRS adoption does not lead to increased earnings quality.…”
Section: Meansupporting
confidence: 86%
“…The studies of Garanina and Kormiltseva (2013) and Outa (2011) however negated the positive effect of IFRS adoption on the value relevance of accounting information. Ismail et al (2013), Sellami and Fakhfakh (2013), Assidi and Omri (2012) and Sun et al (2011) noticed increases in earnings quality in the post IFRS periods. However, the works of Ames (2013), Nullah (2013) and Hoque et al (2012) showed that earnings portrayed lower persistency and predictability after IFRS adoption.…”
Section: Introductionmentioning
confidence: 93%
“…The similar findings was highlighted in the study by Sellami and Fakhfakh (2013) where the Dechow et al (1988) model were exploited to show a decrease in absolute value of discretionary accruals among a sample of 124 French companies during the post-IFRS period. It was also suggested that improvements in accounting standards led to the lessening of earnings management, further timely loss recognition and improved value relevance among these listed firms in the London Stock Exchange during the 2004 and 2005 period (Iatridis, 2010).…”
Section: Ifrs Improves Accounting Quality By Reducing Earnings Managesupporting
confidence: 79%